(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background and Aims: Supraglottic airway devices have been established in clinical anesthesia practice and have been shown to be safe and efficient. The objective of this, randomized trial was to compare I-Gel with LMA-Proseal in anesthetized spontaneously breathing patients. Material and Methods: 100 patients all asa 1 & 2 undergoing short surgical procedures were randomly assigned to I-gel (Group X) or LMA- Proseal (Group Y). Anesthesia was induced with standard doses of propofol and the supraglottic airway device was inserted. We compared the ease and time required for insertion, airway sealing pressure and adverse events. Results: There were no significant differences in demographic and hemodynamic data. I-gel was significantly easier to insert than LMA-Proseal (P < 0.05) (Chi-square test). The mean time for insertion was more with Group P (41 + 09.41 secs) than with Group I (29.53 + 08.23 secs) (P < 0.05). Although the airway sealing pressure was significantly higher with Group P (25.73 + 02.21 cm of H 2 O), the airway sealing pressure of Group I (20.07 + 02.94 cm of H 2 O) was very well within normal limit (Student’s t test). The success rate of first attempt insertion was more with Group I (P < 0.05). There was no evidence of airway trauma, regurgitation and aspiration. Sore throat was significantly more evident in Group P. Conclusion: I-Gel is a innovative supraglottic device with acceptable airway sealing pressure, easier to insert, less traumatic with lower incidence of sore throat. Hence I-Gel can be a good alternative to LMA-Proseal.